Three-Dimensional Mathematical Investigation of Dynamic and Hydrostatic Pressure Distributions on Planing Hulls. (5th September 2013) - Ghadimi, Parviz; Tavakoli, Sasan; Dashtimanesh, Abbas; Djeddi, Seyed Reza
Abstract : A mathematical model is utilized in order to calculate three-dimensional pressure distributions on planing hulls. This type of modeling is able to determine the hydrodynamic and hydrostatic pressures acting on the bottom of these hulls. As a result, the total 3-dimensional pressure exerted on the planing hull as a sum of hydrostatic and hydrodynamic pressures can be evaluated. Empirical equations introduced in previous works have been used as the fundamentals for the present mathematical modeling method. The obtained results are compared against available experimental results and results of empirical equations in order to validate the proposed method. The outcome of theR -squared tests conducted on these comparisons shows favorable accuracy of the results. After evaluation of hydrodynamic pressure, the effects of trim and deadrise angles and wetted length on the 3-dimensional pressure distribution are analyzed. Finally, the total pressure on planing hull and the effect of velocity coefficients are studied.